Prevalence and Predictors of Exclusive Breastfeeding Practices In Seberang Ulu I, Palembang: A Cross-Sectional Study (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2019)
Exclusive breastfeeding is one of the successful indicators in improving the health of babies. From 2013 until 2014, the practice of exclusive breastfeeding has decreased in Indonesia and has not reached the national targets of around 80% of babies being exclusively breastfed. This study aimed to identify the prevalence and determinants of exclusive breastfeeding in Seberang Ulu I, Palembang. A community-based cross sectional study was executed from July 5, 2016 to August 5, 2016 among mothers who had infants aged less than six months. A purposive sampling technique was used to select a sample of 125 participants. Data were collected using a structured questionnaire by the face-to-face interview technique. Bivariate and multiple logistic regression analysis were used to determine factors associated with the practice of breastfeeding exclusively and to control confounding effects. The prevalence of exclusive breastfeeding was 26.4% (95% CI: 20.0%-35.1%). After adjusting for confounders (mothers’ attitudes and health workers’ support), mothers who had good knowledge were 11.66 times more likely to breastfeed exclusively than those who had poor knowledge (AOR: 11.66, 95% CI: 3.07-44.31). The prevalence of exclusive breastfeeding in Seberang Ulu I, Palembang, was still very low and has not reached the national target. The recommendation is to maximize the role of health workers in providing information about exclusive breastfeeding, so that they can continue providing motivation for mothers, husbands and families, so that the success and sustainability of exclusive breastfeeding practices could be achieved. Keywords: Mother’s knowledge, mother’s attitude, health workers support, exclusive breastfeeding